A Focus Group Study on African American Living Donors' Treatment Preferences, Sociocultural Factors, and Health Beliefs About Apolipoprotein L1 Genetic Testing. (September 2019) - Gordon, Elisa J.; Amórtegui, Daniela; Blancas, Isaac; Wicklund, Catherine; Friedewald, John; Sharp, Richard R.
Introduction: Because apolipoprotein L1 ( APOL1 ) risk variants may contribute to live donors' kidney failure postdonation, professional guidelines suggest informing potential donors with African ancestry about the availability of APOL1 genotyping. This study assessed African American (AA) donors' perceptions of APOL1 genetic testing and how APOL1 may affect ethnic identity. Methods/Approach: Four focus groups were conducted with AA donors about their decision-making for and perceptions of APOL1 genetic testing and donation to inform a new culturally targeted educational brochure on APOL1 genetic testing. Qualitative data were analyzed by thematic analysis. Findings: Seventeen donors participated (47% participation rate). Four major themes emerged. (1) In hypothetical scenarios, most participants would have undergone APOL1 testing during donor evaluation to make a more informed decision, but many would have still donated. (2) Participants desired information about how having 2 APOL1 risk variants affects the donor's and the recipient's health. (3) Participants referred to diversity of genetic ancestry and cultural constructions of racial/ethnic identity to question the population at risk for APOL1 risk variants and recommended that all potential donors undergo genetic testing and receive education about APOL1 . (4) Participants worried that out-of-pocket costs would deter APOL1 testing and that APOL1 could become a preexisting condition and discriminate against AAs. Discussion: Our findings suggest that AA donors desire APOL1 testing to foster informed consent. Transplant clinicians should be aware of these responses to APOL1 testing and be sensitive to historical issues of distrust and discrimination.